The international communication of tik tok short video of Chinese opera culture - Yang Yuejia; Lee Kuok Tiung (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
The progress of Internet technology has had a profound impact on the field of communication. The innovation of visual technology makes new media gradually replace traditional media as the main media of communication. The international communication of Chinese opera culture is in a critical period of strategic change. This paper applies content analysis method to study the most visible videos of Chinese opera culture on Tik Tok, a platform of international use and satisfaction theory, and analyses them from three dimensions: communication subject, communication content and audience participation. It is found that the communication of Chinese opera culture on the new media video social platform Tik Tok generally presents the characteristics of large internal differences, high diversity but tend to focus, positive attitude but low interaction, indicating that the Chinese opera culture has achieved good results in international communication with the help of new media, but there are still some shortcomings. The dissemination of Chinese opera culture with the help of international new media video should encourage individuals to publish, enrich and innovate the content and form of communication, increase the content of popular science education, and tell the story of Chinese opera culture, so as to better establish the international image of Chinese opera culture.